(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Internet Technology implies that bullying is not restricted to schools, colleges, universities or road places. Internet means Cyberbullying can take place anytime, anywhere, even at playground, home etc, via smart devices, emails, SMS, WhatsApp messages, and social media, 24 * 7 * 365. Due to Information and Communication Technologies, cyberbullies can happen to annoy, endanger, or embarrass anyone from any part of the world. Cyberbullying Instances has dangerous concerns such as mentally disorder, suicide is now regularly stated in most of the media houses. Social media like Twitter, YouTube, Facebook, and Instagram and Messaging system like WhatsApp, Kik etc have been listed as the top groups with the maximum proportion of consumers registering problems of cyberbullying. In our proposed framework, we extract the cyberbullying from Twitter Tweets based on Machine Learning.